Shape of light : 100 years of photography and abstract art - Baker, Simon; de l'Ecotais, Emmanuelle (London: Tate Publishing, 2018)
"Edited by Simon Baker and Emmanuelle de l'Ecotais; with Shoair Mavlian; with contributions by Sarah Allen, Simon Baker, Emmanuelle de l'Ecotais, Emma Lewis, Shoair Mavlian Published on the occasion of the exhibition 'Shape of light : 100 years of photography and abstract art'; Tate Modern, London, 2 May - 14 October 2018"